Impact of the proposed changes to nutrition fact panel on consumer perception - Smieja, Erin Marie (Kansas State University, 2018)
Background: The US Food and Drug Administration proposed various updates to the nutrition fact panel, which included change to font, type size, addition of nutrients, and declaring absolute values. The rational was the new panel will provide consumers with more accurate and clear information, which may result in better food choices. Objective: This study examines whether participants perception of nutrient information and/or sensory properties will change based on proposed nutrition panel display format. Design: An online questionnaire was developed, and participants were randomized and selected to view the current nutrition label or the proposed nutrition label. The questionnaire was divided into three parts; (1) demographic information, (2) questions related to specific items of interest on the nutrition panel, (3) responses to questions after viewing each of five different food labels. Subjects/Setting: US food shoppers over 18 years of age who read food labels (n=1221) completed the online questionnaire. Statistical Analysis: Descriptive statistics were used for the analysis of participants demographic information. A Chi-square test were applied to test for significant differences between the current and proposed nutrition panels. Results: The study reveals that the top items of interest and importance viewed on both the proposed and current nutrition panel were similar. More than 30 percent of participants selected added sugar, sugar, and sodium, may affect sensory characteristic. The nutrition panels showed distinct differences in descriptive attributes across the five food categories, and significant differences between the current and proposed labels included “too sweet,” “nutritious,” “healthy,” “nutrient dense,” “balanced nutrition” and “artificial”. Conclusion: Consumers’ perceptions are impacted with the proposed nutrition panel. This study emphasized that consumers may be unclear about the labeling of added sugar. Government agencies, industry and those who impact health care will need to provide additional education to make sure consumers are clear about the labeling of added sugar.
Keywords: Nutrition labeling; Nutrition policy; Consumer behavior; Food consumption; Food label use